Prevalence of poor sleep quality and its association with body mass index among undergraduate medical students - Kumar Karki, Prabin; Khakurel, Gita; Shrestha, Biju; Gautam, Kalyan (Journal of Chitwan Medical College, 2025)
Introduction: Sleep quality is a crucial determinant of physical and mental health, and poor sleep is commonly reported among medical students due to academic stress and lifestyle factors. This study aimed to assess the prevalence of poor sleep quality among medical students and its association with body mass index (BMI) and gender. Method: A cross-sectional study was conducted among undergraduate medical students of Kathmandu Medical College, Nepal, from Jun to Aug, 2025. Ethical approval was obtained. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Normally distributed continuous variables were presented as mean±SD, categorical variables are presented as n(%). %). The IBM-SPSS was used for statistical analysis to find out associations between sleep quality, BMI, and gender using the Chi-square test, with a significance level set at p<0.05. Result: Among 269 participants, 117(43.5%) reported poor sleep quality, while 152 (56.5%) had good sleep quality. The prevalence of poor sleep quality was slightly higher among overweight students (29/53, 54.7%) compared to normal-weight (68/175, 38.9%) and underweight students (20/41, 48.8%), though association was not statistically significant (p=0.095). Gender showed a significant association with sleep quality: males had a higher prevalence of poor sleep quality (75/151, 49.7%) than females (43/118, 36.4%) (p=0.047). Conclusion: Poor sleep quality affects nearly half of medical students in this study, more in males, highlighting the need for targeted interventions to promote healthy sleep habits.